2007
DOI: 10.1080/09737189.2007.11885241
|View full text |Cite
|
Sign up to set email alerts
|

Quality Science Education at Secondary School Level in Delta State: Are the Libraries and Science Books Available for Use?

Abstract: The purpose of this study was to find out the state of science books in libraries in Public Schools in Delta State of Nigeria and to particularly determine the positioning of the libraries for the effective implementation of the senior secondary science curriculum -in the areas of kinds of books available, their quantity, quality and relevance. The design employed for the study was survey. To guide this study, five research questions were raised and answered. 90 Public secondary schools randomly selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…They also showed that the correlation between the level of motivation and the achievements scores is moderate but statistically significant. That motivation can significantly influence students' achievement scores in science was also revealed in the studies of Patrick et al (2007) and Cavas (2011).…”
Section: The Influence Of Students' Formal Reasoning Abilities and In...mentioning
confidence: 63%
“…They also showed that the correlation between the level of motivation and the achievements scores is moderate but statistically significant. That motivation can significantly influence students' achievement scores in science was also revealed in the studies of Patrick et al (2007) and Cavas (2011).…”
Section: The Influence Of Students' Formal Reasoning Abilities and In...mentioning
confidence: 63%
“…Intrinsische Motivation, extrinsische Motivation und Lernverhalten beeinflussen gemeinsam die Lernleistung (siehe auch Tokan & Imakulata, 2019a). Auch in größer angelegten Studien konnten Belege für die positiven Effekte motivationaler Aspekte auf die Lernleistung von Schülerinnen und Schülern gefunden werden (Cavas, 2011;Patrick et al, 2007). Jedoch mutet das methodische Vorgehen dieser Untersuchungen durch direkte Instruktion der Proband:innen teils eher unorthodox an (Patrick et al, 2007).…”
Section: Bezüge Der Motivation Zu Weiteren Theoretischen Konstruktenunclassified
“…Auch in größer angelegten Studien konnten Belege für die positiven Effekte motivationaler Aspekte auf die Lernleistung von Schülerinnen und Schülern gefunden werden (Cavas, 2011;Patrick et al, 2007). Jedoch mutet das methodische Vorgehen dieser Untersuchungen durch direkte Instruktion der Proband:innen teils eher unorthodox an (Patrick et al, 2007). Im deutschsprachigen Raum konnten Steinmayr und Spinath (2009) Motivation als Prädiktor für schulische Leistung identifizieren.…”
Section: Bezüge Der Motivation Zu Weiteren Theoretischen Konstruktenunclassified